The Role of International Legal Cooperation in Combating Transnational Drug Networks in Indonesia - Dody Cindur Mato; Muhammad Syaroni Rofii (Green Publisher Indonesia, 2026)
Transnational narcotics crime represents a serious threat to national security and social stability in Indonesia. The cross-border nature of this crime makes international legal cooperation an essential instrument in combating transnational narcotics networks. This study aimed to analyze the role and implementation of international legal cooperation in addressing transnational narcotics networks in Indonesia, identify legal, institutional, and technical challenges, and formulate effective and sustainable strategies to strengthen cooperation mechanisms. This research employed a qualitative method using a normative juridical approach and an analysis of international cooperation practices. The findings indicated that, although Indonesia has actively participated in various international cooperation mechanisms, their effectiveness remains constrained by differences in legal systems, limitations in extradition procedures and mutual legal assistance (mutual legal assistance), and inadequate institutional coordination. Therefore, strengthening strategies are required, including harmonizing national legislation, optimizing international cooperation frameworks, and improving institutional capacity and law enforcement technology.